2011
DOI: 10.1089/rej.2010.1109
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine Exerts Toxic Effects on Subventricular Zone Stem/Progenitor Cells and Inhibits Neuronal Differentiation

Abstract: Methamphetamine (METH) is a potent and widely consumed psychostimulant drug that causes brain functional and structural abnormalities. However, there is little information regarding METH impact on adult neurogenic niches and, indeed, nothing is known about its consequences on the subventricular zone (SVZ). Thus, this work aims to clarify the effect of METH on SVZ stem/progenitor cells dynamics and neurogenesis. For that purpose, SVZ neurospheres were obtained from early postnatal mice and treated with increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…The proliferation of both adult hippocampal and striatal progenitor cells in vivo is frequently assessed by 5-bromo-2′-deoxyuridine (BrdU) incorporation (a thymidine analogue incorporated during DNA synthesis) or Ki67 antigenicity (a nuclear protein associated with cell division) (Scholzen & Gerdes, 2000) in species including rats, mice, and gerbils (Teuchert-Noodt, Dawirs, & Hildebrandt, 2000; Mao & Wang, 2001; Mandyam, Wee, Eisch, Richardson, & Koob, 2007; Yuan, Quiocho, Kim, Wee, & Mandyam, 2011). Similar effects are seen in vitro , where survival is also variably reduced (Tian, Murrin, & Zheng, 2009; Venkatesan et al, 2011; Bento, Baptista, Malva, Silva, & Agasse, 2011). These effects have been correlated to enhanced nitration and modification of function of key metabolic proteins (Venkatesan et al, 2011).…”
Section: Neural/glial Progenitors and Hivsupporting
confidence: 56%
“…The proliferation of both adult hippocampal and striatal progenitor cells in vivo is frequently assessed by 5-bromo-2′-deoxyuridine (BrdU) incorporation (a thymidine analogue incorporated during DNA synthesis) or Ki67 antigenicity (a nuclear protein associated with cell division) (Scholzen & Gerdes, 2000) in species including rats, mice, and gerbils (Teuchert-Noodt, Dawirs, & Hildebrandt, 2000; Mao & Wang, 2001; Mandyam, Wee, Eisch, Richardson, & Koob, 2007; Yuan, Quiocho, Kim, Wee, & Mandyam, 2011). Similar effects are seen in vitro , where survival is also variably reduced (Tian, Murrin, & Zheng, 2009; Venkatesan et al, 2011; Bento, Baptista, Malva, Silva, & Agasse, 2011). These effects have been correlated to enhanced nitration and modification of function of key metabolic proteins (Venkatesan et al, 2011).…”
Section: Neural/glial Progenitors and Hivsupporting
confidence: 56%
“…Also, METH induces long-term effects in SGZ stem/progenitor cell proliferation, as described by Schaefers et al (2009) showing that a single METH administration (50 mg/kg) to 14-day-old gerbils decreases the number of BrdU-positive cells, 45 days post-administration. In addition, our group demonstrated that 100 μM METH (48 h of exposure) reduced proliferation in SVZ cultures (Bento et al, 2011).…”
Section: Discussionmentioning
confidence: 84%
“…Additionally, our group recently verified that a nontoxic concentration of METH (1 nM for 7 days) decreased the number of mature neurons in DG-derived neurosphere cultures (Baptista et al, 2012). Concerning the subventricular zone (SVZ), we have also shown that METH decreases cell proliferation, neuronal differentiation and maturation of stem/progenitor cells (Bento et al, 2011).…”
Section: Introductionmentioning
confidence: 71%
“…The neurotoxicity associated with MA is attributed to increased oxidative stress, dopamine dysfunction, mitochondrial dysfunction, excitotoxicity, alteration in BBB integrity, inflammatory mechanisms and defective neurogenesis [31] , [33] . In particular, MA has been shown to inhibit neurogenesis in subventricular and hippocampal progenitor cells [34] , [35] . In addition, classical fMRI study on MA demonstrated reduced striatal volumes in children with prenatal MA exposure.…”
Section: Discussionmentioning
confidence: 99%